Polymeric Nanosponges for Improving the Solubility of Enzalutamide: Design and Characterization - Kapil Jibhau More; Yogesh P. Sharma (Asian Journal of Pharmaceutical Research and Development, 2026)
Despite being clinically efficacious as an androgen receptor (AR) antagonist in the treatment of CRPC, Enzalutamide (ENZ) is classified as Biopharmaceutics Classification System (BCS) Class II drug owing to its high membrane permeability and poor aqueous solubility (about 3 µg/mL at physiological pH). These physicochemical properties make enzalutamide less dissolvable and orally bioavailable when formulated inadequately. Therefore, there exists an urgent need to develop novel strategies of drug delivery that address the dissolution problem and enhance the efficacy of the drug. NS refer to a relatively new category of three-dimensional porous polymer-based nano-materials that have ability to incorporate hydrophobic drugs inside their cavity using mechanisms of complexation, adsorption, and physical incorporation. Nanosponges are designed to enhance the aqueous solubility of crystalline drugs by transforming them to amorphous forms, enlarging their surface area exposed to dissolution medium, enhancing wettability of the drug molecules, and facilitating sustained release.The fabrication of nanosponges is carried out using polymers like cyclodextrin derivatives, ethyl cellulose, Eudragit, hydroxypropyl methylcellulose, which are crosslinked with cross-linking materials like diphenyl carbonate, pyromelliticdianhydride, carbonyldiimidazole. The crucial aspects of nanoparticle characterization like particle size, polydispersity index, zeta potential, entrapment efficiency, X-ray diffraction, differential scanning calorimetry, and in vitro drug release profiles have been critically analyzed in this review. Additionally, the mechanisms behind the improvement of the solubility of drugs, the advancements made in nanocarriers for enzalutamide, their applications in oral and targeted anticancer drug delivery, and the translational issues to be addressed before their application in humans have been highlighted in this review. It is evident from this review that nanosponge carriers hold tremendous promise for the treatment of prostate cancer.